2021
DOI: 10.4049/jimmunol.2001191
|View full text |Cite
|
Sign up to set email alerts
|

TLR-4 Agonist Induces IFN-γ Production Selectively in Proinflammatory Human M1 Macrophages through the PI3K-mTOR– and JNK-MAPK–Activated p70S6K Pathway

Abstract: IFN-γ, a proinflammatory cytokine produced primarily by T cells and NK cells, activates macrophages and engages mechanisms to control pathogens. Although there is evidence of IFN-γ production by murine macrophages, IFN-γ production by normal human macrophages and their subsets remains unknown. Herein, we show that human M1 macrophages generated by IFN-γ and IL-12– and IL-18–stimulated monocyte-derived macrophages (M0) produce significant levels of IFN-γ. Further stimulation of IL-12/IL-18–primed macrophages or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Multicellular organisms face an additional obstacle because their defenses arise from a multitude of cells, each of which has both limited information and limited agency [ 4 , 57 , 58 ], but which together form the powerful, perilous collective. TLR signaling and induced cytokine secretion, for example, occur at a cellular scale [e.g., TLR-2, -3, or -4 agonists induce interferon (IFN)-γ production by human M1-like inflammatory macrophages in vitro [ 59 ]], but affect fitness at the organismal scale (e.g., strong IFN-γ responsiveness is essential for controlling chronic pulmonary aspergillosis and extending the life of human patients [ 60 ]). Similarly, sensitive cellular detection of LPS by a wide array of host species [ 61 ] may translate into disastrously potent cytokine responses and life-threatening septic shock at the organismal scale (e.g., in C57BL/6 mice injected with LPS [ 62 ]).…”
Section: Legacies Of Multicellularity That Confer Susceptibility To Immunopathologymentioning
confidence: 99%
“…Multicellular organisms face an additional obstacle because their defenses arise from a multitude of cells, each of which has both limited information and limited agency [ 4 , 57 , 58 ], but which together form the powerful, perilous collective. TLR signaling and induced cytokine secretion, for example, occur at a cellular scale [e.g., TLR-2, -3, or -4 agonists induce interferon (IFN)-γ production by human M1-like inflammatory macrophages in vitro [ 59 ]], but affect fitness at the organismal scale (e.g., strong IFN-γ responsiveness is essential for controlling chronic pulmonary aspergillosis and extending the life of human patients [ 60 ]). Similarly, sensitive cellular detection of LPS by a wide array of host species [ 61 ] may translate into disastrously potent cytokine responses and life-threatening septic shock at the organismal scale (e.g., in C57BL/6 mice injected with LPS [ 62 ]).…”
Section: Legacies Of Multicellularity That Confer Susceptibility To Immunopathologymentioning
confidence: 99%
“… 81 More recently, innate immune signaling through TLR4, the LPS receptor, has also been found to involve mTORC1/2 and the JNK and MAPK pathways. 82 We suggest that all of the observations from both this study and prior in vitro and in vivo studies can be explained by ADI-dependent depletion of arginine pools and inactivation of mTORC1 of host cells, with the possible qualification that it would likely be a localized effect in vivo, i.e . affecting intestinal epithelia and gut-associated immune cell populations, rather than systemic effects.…”
Section: Discussionmentioning
confidence: 55%
“…The activation of mTOR (mechanistic target of rapamycin), LAT (linker for activation of T cells), PI3K (phosphoinositide 3-kinase), AKT (protein kinase B), JNK (c-Jun N-terminal kinases), RIP3K (receptor-interacting protein kinase 3), ERK (extracellular signal-regulated kinase), and p38-MAPK (p38 mitogen-activated protein kinases) signaling causes the massive production of IFN-α, IFN-β, IFN-γ, IL1 α, IL1 β, TNF α, IL6, IL12, IL17, and C5a [ 325 , 326 , 327 , 328 , 329 , 330 , 331 , 332 , 333 , 334 , 335 , 336 , 337 ]. Studies have demonstrated the involvement of several of the signaling cascades in lysosomal storage diseases, particularly in the context of disease pathogenesis and potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%